폴리염화비닐의 탈염화수소에 의한 전도성 고분자의 합성과 전기유변 거동 - 김정우 (The Graduate School, Ajou University, 2005)
Dehydrochlorinated poly(vinyl chloride) was synthesized and electrorheological (ER) properties of its suspension in silicone oil were investigated. The structure of the dehydrochlorinated PVC is polyacetylene-like and has relatively long polyene sequences. It shows electric conductivity in the order of 10-8 S/cm without any doping process. The synthesized polymer was characterized by Fourier Transform Infrared Spectroscopy (FT-IR) and Elemental analysis. Rheological measurements were carried out using a rotational rheometer with high voltage generator in both constant shear stress and rate modes. Suspensions of the synthesized PVC particles in silicone oil showed a substantial ER response.
학위논문(석사)--아주대학교 대학원 :화학공학과,2005